دراسة تأثير الغمر بالماء على معامل المرونة والصالدة لمتر اكب بوليمري من البولي اثيلين عالي الكثافة المدعم بألياف الزجاج - حسن سلمى محمد; سلطان عفاف فاضل; حسن نادية محمد (Al-Nahrain Journal of Science, 2018)
Elastic modulus (E) and surface indentation of composite materials that consist of high density polyethylene (HDPE) reinforced with (30 wt %) ratio of glass fiber have been studied. Comparison is made between the properties of composite at different immersion times (8, 16, 24) days and also the physical properties characteristics are studied by a absorption tests for all samples included diffusion coefficient by immersing them for a period of time in water and then calculated. It was found that elastic modulus, and surface indentation and diffusion coefficient for (HDEP) increases when the materiel is reinforced with fiber, while it decreases when the immersion time increases